Vision 2020, the Multimedia Supercorridor and Malaysian Universities - Vicziany, Marika; Puteh, Marlia (Asian Studies Association of Australia, Inc., 2004)
Malaysia is one of the most ‘globalised’ countries in the Asian region. This statement is based on Kearney’s ranking of 62 countries using 14 indicators to test the degree of globalisation. Table 1 ranks some of the important Asian countries - from those that are the least integrated into the world system to the most integrated. Integrated and globalisation in this sense, are used as synonyms throughout this paper. Malaysia’s global position in 2004 reflected the achievements of the previous decades. In the 1990s, for example, the Malaysia government decided push the country in the direction of transforming itself from an industrial base into a K-economy based on knowledge and information technology. The universities were expected to play a role in this, but have they? This paper seeks to map out the contours of Malaysia’s integration in the world system, how this relates to Mr Mahathir’s ‘Vision 2020’ and finally how all of this has impacted on the higher educational sector.